A longitudinal study of Dominican secondary school students and their perceptions of a multi-hazard environment - Parham, Martin (My University, 2020)
Risk perception studies compare differences in objective and actual risk and form an essential part of disaster risk reduction (DRR). Criticisms of past risk perception studies emphasise the narrow focus on single hazard environments; focus on just adult groups and short-term approaches. This study addresses these issues through a 5-year longitudinal study (2013-2018) of student perception on the Small Island Developing State (SIDS) of Dominica, to better understand multi-hazard perception trends. As part of this assessment, it uses the 2012 UNESCO report into disaster risk education to test the impact of three educational approaches (interactive, surrogate, field-based) on changing student risk perception. Criticisms of existing student risk perception studies focus on methods deemed more applicable to adults. This study tests an adapted Pictorial Representation of Individual Self Measure (PRISM) method to assess its validity for collecting child risk perception data. This study, one of the first longitudinal studies assessing multi-hazard perception, showed that PRISM was an effective tool for collecting secondary student risk perception data. Longitudinal trends in multi-risk perception showed consistent student perceived relative risk order. Students showed bias towards perceptions of known or experienced hazards and poor relative understanding of low frequency high magnitude geophysical hazards. Significant large-scale events (e.g., Hurricane Maria) intensified hazard perceptions, however, this effect decayed over time. Highlighting that the relationship between frequent versus less frequent hazards needs further consideration. Equally, location and gender are both factors influencing perception. Boys tended to be more risk averse, while evidence of disaster risk perception spatially suggests a need for bespoke approaches to DRR education. This study showed that targeted educational pedagogical approaches all impacted risk perception. Participatory approaches were more impactful. Field-based learning caused the greatest shifts in perceptions for less-perceived geophysical hazards. This has important implications for future disaster risk education and outreach. The study showed that careful educational resourcing can improve engagement in DRR, but it should have a local focus. This study underlines the need to develop DRR education into school curriculum. Children should be encouraged to play a more active role in bottom up DRR approaches, within schools to improve risk perceptions.
Keywords: Dominica; secondary school; multi-hazard environment; disaster risk reduction; student risk perception